The Variable Nature of Vitamin C-Does It Help When Dealing with Coronavirus? - Katarzyna Grudlewska-Buda; Natalia Wiktorczyk-Kapischke; Anna Budzyńska; Joanna Kwiecińska-Piróg; Jana Przekwas; Agnieszka Kijewska; Dominika Sabiniarz; Eugenia Gospodarek-Komkowska; Krzysztof Skowron (MDPI AG, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is still spreading worldwide. For this reason, new treatment methods are constantly being researched. Consequently, new and already-known preparations are being investigated to potentially reduce the severe course of coronavirus disease 2019 (COVID-19). SARS-CoV-2 infection induces the production of pro-inflammatory cytokines and acute serum biomarkers in the host organism. In addition to antiviral drugs, there are other substances being used in the treatment of COVID-19, e.g., those with antioxidant properties, such as vitamin C (VC). Exciting aspects of the use of VC in antiviral therapy are its antioxidant and pro-oxidative abilities. In this review, we summarized both the positive effects of using VC in treating infections caused by SARS-CoV-2 in the light of the available research. We have tried to answer the question as to whether the use of high doses of VC brings the expected benefits in the treatment of COVID-19 and whether such treatment is the correct therapeutic choice. Each case requires individual assessment to determine whether the positives outweigh the negatives, especially in the light of populational studies concerning the genetic differentiation of genes encoding the solute carriers responsible forVC adsorption. Few data are available on the influence of VC on the course of SARS-CoV-2 infection. Deducing from already-published data, high-dose intravenous vitamin C (HDIVC) does not significantly lower the mortality or length of hospitalization. However, some data prove, among other things, its impact on the serum levels of inflammatory markers. Finally, the non-positive effect of VC administration is mainly neutral, but the negative effect is that it can result in urinary stones or nephropathies.